In-coating graphene nano-platelets for environmentally-friendly corrosion protection of iron - Jenny Baker (Corrosion Science, 2017)
A primer coating system adherent to iron substrates based on graphene nano-platelets (GNPs) dispersed in polyvinylbutyral (PVB) is presented. Using a scanning Kelvin probe (SKP), the composite coatings are shown to exhibit exceptional resistance to an important corrosion-driven failure process, namely cathodic delamination, when aqueous chloride electrolyte is introduced to a penetrating coating defect. Delamination rate kinetics are shown to correlate strongly with reductions in the rate of oxygen permeation through the coating with increasing GNP pigment volume fraction.